The category motto in today’s literary studies - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
In the contemporary literary studies, the category ‘motto’ has a well-established position, although one often meets an opinion that a uniform theory of universal motto has not been developed yet. This article is an attempt to synthesise the existing findings about the motto. It presents an overview of the most interesting research positions. This allows us to illustrate, in general terms, how the meaning of the motto changed from the sixteenth to the eighteenth century, and how it evolved from a very general blurry meaning to the one representing the main characteristics of intertextuality.